2020
DOI: 10.1093/hmg/ddaa248
|View full text |Cite|
|
Sign up to set email alerts
|

Ceramide contributes to pathogenesis and may be targeted for therapy in VCP inclusion body myopathy

Abstract: Background/Objective Knock-in homozygote VCPR155H/R155H mutant mice are a lethal model of Valosin Containing Protein (VCP)-associated Inclusion Body Myopathy, Paget disease of bone, frontotemporal dementia, and amyotropic lateral sclerosis. Ceramide (d18:1/16:0) levels are elevated in skeletal muscle of the mutant mice, compared to wild-type controls. Moreover, exposure to a lipid-enriched diet reverses lethality, improves myopathy and normalizes ceramide levels in these mutant mice, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Hence, the preservation of the function of these pathways may have contributed to the improved health span in aged mice and increased life span in worms treated with myriocin. This is consistent with previous reports showing that ceramides are key signaling contributors to the pathogenesis of various proteotoxic neuromuscular diseases such as Parkinson's disease, progressive cerebello-cerebral atrophy type 2, Huntington's disease, spinal muscular atrophy, and valosin-containing protein (VCP)-associated inclusion body myopathy (43,(48)(49)(50). Given the known effects of ceramides on human pathophysiology, such as in insulin resistance, dyslipidemia, and cardiovascular diseases (19)(20)(21)(22), it will be of interest to study whether ceramide dysregulation also causes proteotoxicity in these obesity-fueled disorders.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the preservation of the function of these pathways may have contributed to the improved health span in aged mice and increased life span in worms treated with myriocin. This is consistent with previous reports showing that ceramides are key signaling contributors to the pathogenesis of various proteotoxic neuromuscular diseases such as Parkinson's disease, progressive cerebello-cerebral atrophy type 2, Huntington's disease, spinal muscular atrophy, and valosin-containing protein (VCP)-associated inclusion body myopathy (43,(48)(49)(50). Given the known effects of ceramides on human pathophysiology, such as in insulin resistance, dyslipidemia, and cardiovascular diseases (19)(20)(21)(22), it will be of interest to study whether ceramide dysregulation also causes proteotoxicity in these obesity-fueled disorders.…”
Section: Discussionsupporting
confidence: 93%
“…A recent report found that motor neurons from ALS patients with p97 mutations exhibited more contacts between the ER and mitochondria relative to controls 60 . Furthermore, several studies suggest that a lipid-controlled diet or modulation of lipid biosynthesis may have therapeutic implications in mouse models of p97 proteinopathies 61 , 62 . Thus, altered organelles contacts and downstream lipid synthesis warrants further investigation in p97 associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with Dr. Daniele Piomelli (University of California, Irvine), they found they could inhibit ceramide biosynthesis by targeting serine palmitoyltransferase (SPT) to effectively reduce ceramide levels in mouse and human primary myoblasts. This inhibition reduced various markers of disease including reducing cytoplasmic TDP-43, autophagy markers, LC3B and p62, and ubiquitin ( Weiss et al, 2021 ). It should be noted that mutations in SPT are linked to hereditary sensory neuropathy type 1.…”
Section: Session 1 Introduction To Vcp Disease: Discussion Of Clinica...mentioning
confidence: 99%